Utilization of oligosaccharides component from soybean meal and sweet potatoes on broiler feed - Haryati, Tuti; ., Supriyati (Indonesian Animal Sciences Society, 2010)
The investigation was carried out to study the effect of oligosaccharides from soybean meal (SBM) and sweet potatoes as feed additives on feed to improve the productivity of broiler. The amounts of 704 day-old chicks from Arbor Arcres were randomly distributed into 16 treatments with 4 repetionsÂ and with 11 chicks in each pens. The treatmentsÂ were: 2 level of sweet potato oligosaccharides (0.1 and 0.2%), 2 levels of residue ofÂ sweet potato extracts (0.4 and 0.8%), 2 levels of SBM oligosaccharides (0.1 and 0.2%), 2 levels of residue of SMB extracts, 2 levels of MOS commercial (0.01 and 0.02%) 2 levels of commercial inulin (0.1 and 0.5%), 2 levels of commercial FOS (0.2 and 0.4%) and control with and without antibiotic. The results showed that better FCR (P < 0.05) was seen on the addition of 0.2% sweet potato oligosaccharides at 3 weeks trial, meanwhile on 0.1% addition was able to improved the absorption of Ca and P. The trial up to 5 weeks, only treatment with 0.8% of residue have a better FCR value (P < 0.05). The effect of utilization of SMB oligosaccharides was only observed on 0.8% residue at 5 weeks trial which have a better FCR value. It could be concluded that the extract of oligosaccharides from soybean meal and sweet potatoes could improve the effisiency of broiler feed. Key Words: Oligosaccharides, Sweet Potato, Soy-Bean Meal, Productivity, Broiler